Where Island Studies Meets Mobility Studies in Literary and Cultural Studies: Part Two - Reyes, Maria Luisa T. (Archīum Ateneo, 2024)
This article describes the second part of the special section to highlight how the essays provide yet a unique perspective on the interconnections between island studies and mobility studies. From an examination of canonical works from Tatsuhiro Oshiro’s The Cocktail Party to an investigation of more contemporary materials found on media such as YouTube and a Disney film, this article aims to examine how the featured essays closely study the concept of “islands” and how its interconnection with and influence on mobility.